Decreased regulatory T‐cells and CD4+/CD8+ ratio correlate with disease onset and progression in patients with generalized vitiligo. (13th May 2013) - Dwivedi, Mitesh; Laddha, Naresh C.; Arora, Prateek; Marfatia, Yogesh S.; Begum, Rasheedunnisa
Summary The aim of present study was to evaluate CD4+/CD8+ ratio and CD4+CD25hiFoxP3+ Tregs in GV patients with reference to their effect on disease onset and progression. Flow cytometry was used for determination of CD4+/CD8+ ratio and Tregs in 82 patients and 50 controls. CD8+ T‐cell counts were significantly higher in GV patients as compared with controls (p = 0.003). Active GV patients showed higher CD8+ T‐cell counts compared with stable GV patients (p = 0.001). The CD4+/CD8+ ratio decreased significantly in patients as compared with controls (p = 0.001). Moreover, the ratio in active GV patients significantly lowered as compared with stable GV patients (p = 0.002). Significant decrease in Treg cell percentage and counts in GV patients was observed compared with controls (p = 0.009, p = 0.008) with significant reduction in FoxP3 expression (p = 0.024). Treg cell percentage and counts were significantly decreased in active GV patients compared with stable GV patients (p = 0.007, p = 0.002). Our results suggest that an imbalance of CD4+/CD8+ ratio and natural Tregs in frequency and function might be involved in the T‐cell mediated pathogenesis of GV and its progression.